PENGARUH BAURAN PEMASARAN TERHADAP PROSES KEPUTUSAN PEMBELIAN PRODUK ASMORODJATI DI TARUMARTANI COFFEE DAN RESTO 1918 - Dimas Bagus Saputra; Indah Widowati (Agrisociabus, 2023)
This study aims (1) to determine respondents' evaluation of product, price, place, promotion, physical evidence, people, process and purchasing decisions at Tarumartani Coffee and Resto 1918. (2) to analyze the influence of the product marketing mix, price, place, promotions, people, physical evidence, the process of purchasing decisions at Tarumartani Coffee and Resto 1918. This research uses a quantitative descriptive research type using primary data and secondary data. The research implementation method uses the survey method with a questionnaire of 80 respondents. The results of the validity and reliability tests show that the research data is valid and reliable. Respondents' assessment of the product variable has an average score of 3.83, price has an average score of 3.81, place has an average score of 3.58, promotion has an average score of 3.59, people have an average score 3.75, physical facilities have an average score of 3.57, the process has an average score of 3.72 and the purchasing decision process has an average score of 3.8. The test results using multiple linear regression showed that the product, price, place, people, physical facilities, process variables partially influenced the purchasing decision process variables. While the promotion variable has no effect on the purchasing decision process.Keywords : Product, Price, Place, Promotion, People, Physical evidence, Process, Purchase Decision Process